An Impact Study on Working Conditions and Job Satisfaction of Tea Estate Workers in Wayanad District - Mohanasundaram, Dr. A.; NK, SHABARIMOL (INTERNATIONAL JOURNAL OF SCIENTIFIC RESEARCH IN ENGINEERING AND MANAGEMENT, 2025)
Job satisfaction plays a pivotal role in influencing employee performance, retention, and overall organizational success, especially in labor-intensive industries such as tea estates. This study aims to evaluate the job satisfaction levels among employees in the tea estates of Wayanad District and identify the key factors that influence their satisfaction. The research explores various aspects, including working conditions, wages, welfare measures, job security, and management support—elements that directly affect employee morale and productivity. A structured questionnaire was distributed to gather primary data from workers across multiple tea estates in the region. The study utilizes both descriptive and inferential statistical techniques, including Chi-Square tests and correlation analysis, to examine the relationship between demographic variables and job satisfaction. The findings reveal that factors like fair wages, job security, and supportive management practices significantly enhance job satisfaction, while poor welfare measures and substandard working conditions contribute to dissatisfaction. The results offer valuable insights into employee perceptions and challenges within the workplace, emphasizing areas in need of improvement. Based on the findings, the study recommends that estate management focus on improving welfare policies, ensuring equitable wage structures, and creating a more supportive work environment. Such measures are essential for boosting employee retention, productivity, and overall operational efficiency within the tea estate sector. Keywords: Job Satisfaction, Tea Estate, Employee Welfare, Working Conditions, Wayanad, Labor Management, Employee Retention